Consumers' perceived risk and online shopping behaviour of Mudah.my and Lazada.com.my - Khoo, Yen Jin, 1991- author 605006 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2015)
Project Paper (Sarjana Muda Pengurusan (Pemasaran)) - Universiti Teknologi Malaysia, 2015